Effect of Herbicide in Controlling Broadleaf and Sedge Weeds in Wheat (Triticum aestivum L.) (The Agriculturists, 2016)
The study was conducted to assess the effectiveness of herbicide for controlling of weeds in wheat field at FSRD Site, Hatgobindapur, Faridpur during rabi 2011-12 and 2012-13. The experiment was laid out in a RCB design with five replications. There were four treatments viz. U46D fluid, ronstar 25 EC, one hand weeding and control (no weeding). Seven weed species were found in the plots and Cyperus rotundus, Cynodon dactylon, Chenopodium album were the most important weed species. Weed density and dry weight were affected significantly by different treatments. The highest weed dry weight was obtained in control while the lowest dry weight and the highest weed control efficiency were obtained from ronstar 25EC@1 ml/liter water against all types of weed species. Weed control efficiencies of ronstar 25EC against broad leaf, sedge and grass were 92, 86 and 64 %, respectively over control. The lowest weed control efficiency was obtained from one hand weeding treatment, which might be due to lack of proper weeding. Ronstar 25EC produced the highest grain (4.33 t/ha) and straw yields (4.38 t/ha) which were statistically identical to those of U46D fluid. The highest harvest index (49.71%) was found in ronstar 25EC and the lowest (41.89%) was obtained in control. The highest benefit cost ratio (2.30) was obtained from ronstar 25EC that was much higher than hand weeding (1.69). The lowest BCR (1.58) was recorded from the control. It was concluded that herbicide could be a viable alternative of manual weed control practices in wheat cultivation.DOI: http://dx.doi.org/10.3329/agric.v13i2.26588The Agriculturists 2015; 13(2) 54-61